Primary Baerveldt Shunt Implantation: Outcomes and Complications. Issue 2 (December 2016) - Namavari, Abed; Hyde, Robert; Wang, Daniel; Vajaranant, Thasarat; Aref, Ahmad
Abstract Introduction This study is a retrospective case series to evaluate the outcomes and complications of Baerveldt glaucoma implant surgery (BGI) in patients without prior cataract or incisional glaucoma surgery. Methods Patients who underwent 350-mm2 BGI through the Glaucoma Service of the University of Illinois at Chicago between 2010 and 2015 were included in this study. Outcome measures included age, sex, ethnicity, operated eye, preoperative diagnosis, preoperative, and sequential postoperative intraocular pressure (IOP), visual acuity, glaucoma medications, and postoperative complication and interventions. Statistical analyses were performed using the two-sided Studentt test for continuous variables. Results Thirty-seven patients were studied. IOP was consistently and statistically significantly lower at 3 months (17.4 ± 6.4, p  = 3 × 10−7 ), 6 months (13.9 ± 5.1, p  = 2 × 10−11 ), 1 year (12.2 ± 4.0, p  = 9 × 10−10 ), and 2 years (14.6 ± 3.3, p  = 0.0004) postoperatively compared to IOP at baseline (27.5 ± 8.1). Fewer glaucoma medications were used at 3 months (2.8 ± 1.3, p  = 0.04), 6 months (2.6 ± 1.2, p  = 0.02), 1 year (2.7 ± 1.7, p  = 0.04), and 2 years (2.0 ± 1.2, p  = 0.03) postoperatively compared to baseline (3.4 ± 1.1). A total of six cases (16%) had failure. A total of five patients (15%) had postoperative complications. Mean Snellen visual acuity was not statistically different at 6 months (0.5 ± 0.6, p  = 0.88) or 1 year (0.4 ± 0.4, p  = 0.57) postoperatively from baseline (0.5 ± 0.6). Conclusions Primary BGI is effective at reducing IOP and the medication burden in patients suffering glaucomatous optic neuropathy. Further randomized prospective studies are needed to compare various procedures in the primary surgical management of patients with uncontrolled glaucoma. Funding This study was funded by an unrestricted grant from Research to Prevent Blindness.